Ars Vivendi: Spirituality for the End of Life in the 21st century - Mazzini, María Marcela ca. 20./21. Jh. (Concilium, 2021)
In the next few pages I am going to talk about what was known as Ars moriendi in the 14th and 15th centuries and the great tasks these texts pose. Then I will propose an update on these topics, which will enable people in the 21st century to think about a good death.